(untitled) (Fiep Bulletin - online, 2014)
The long-standing presence of physical education (PE) in school curricula suggests that it has passed the test of time as an accepted sphere of formalised educational activity. Indeed, its significance is enshrined in its UNESCO (1978) accorded status of a ‘fundamental human right’ with assured opportunities for practice within education systems. Notwithstanding this status, there has been, and continues to be, world-wide, continental regional and national research evidence pointing to proposals to remove PE from the curriculum, actual and posited reductions in curriculum time allocation, perceived incidences of marginalisation, as well as inadequacies of provision of resources, quality of school PE programmes, inequalities in provision, particularly inclusion of girls and pupils with disabilities and deficiencies in school-wider community partnerships. A concern is that school PE is ‘withering’, i.e.it is in terminal decline. Thus, with the future in mind, the question arises: ‘whither’ physical education?: which direction is it going or do we wish it to go? Is the ‘whither’ in the direction of a ‘Meat Loafesque’ world of dark and insecure gloom and doom or is it a sustai nably positive ‘blue sky’ world in which problem resolution has been secured? This paper considers the research evidence mainly drawn from three World-wide Surveys (Hardman & Marshall, 2000; Hardman & Marshall, 2009; and Hardman, Murphy, Routen and Tones, 2013) conducted over the last two decades on the situation of PE in schools. Particular consideration is given to the general situation of school PE, curriculum time allocation, subject and teacher status, PE curriculumrelated issues, resources (teaching personnel, facilities and equipment), inclusion issues (gender and disability), and school-community pathway links to PE-related activity in out-of-school settings). Concluding comments highlight the key areas of concern in school physical education-related provision and progresses to suggestions for some directions to sustain a secure future for PE as a life-long learning and lifestyle-enhancing enterprise.